Looking behind the terror curtain: A developing world journalism perspective - Kalinga Seneriratne (Asia Pacific Network, 2006)
This article explores and challenges the hypocrisy and misrepresentations surrounding Western media reportage of the global ‘war on terror’.  While the so-called Coalition of the Willing has introduced a rash of new anti-terror laws since 11 September 2001, many of the very freedoms which President Bush said the terrorists were out to destroy, have now been severely curtailed.  This article is also a critique of the dangers of anti-terrorism laws for media seeking to report a complex truth about nationalist struggles.